Stem cell treatment reduces T cell apoptosis in COPD patients with chronic bronchitis but not with emphysema. - KOCAKAYA, DERYA (My University, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is a prevalent and preventable condition. Mesenchymal stem cell (MSC) therapy is being explored to aid in the regeneration of lung cells and airway structure, aiming to restore lung function. Aim: To examine varied responses of MSCs when cultured with peripheral blood mononuclear cells (PBMCs) from different COPD phenotypes, patients were grouped into ACOS, emphysema, and chronic bronchitis categories. Methods: PBMCs from these groups and controls were co-cultured with MSCs derived from dental follicles, revealing differing rates of apoptosis among COPD phenotypes compared to controls. Results: While the chronic bronchitis group exhibited the least lymphocyte viability (p<0.01), introducing MSCs notably enhanced viability across all phenotypes except emphysema, with the chronic bronchitis group showing the most improvement (p<0.05). Conclusion: Stem cell therapy might reduce peripheral lymphocyte apoptosis in COPD, with varying responses based on phenotype, necessitating further research to understand mechanisms and optimize tailored therapies for each COPD subtype.
Keywords: Stem cell; Apoptosis; COPD; Chronic bronchitis; Emphysema